Nursing Care of a Patient With Vogt-Koyanagi-Harada Syndrome With Nystagmus (International Journal of Studies in Nursing, 2022)
Through the nursing of a patient with Vogt Koyanagi-Harada syndrome with nystagmus, the nursing experience was summarized to make the nursing staff more fully understand the nursing methods of the patient with Vogt Koyanagi-Harada syndrome. Through comprehensive risk assessment of the patient, nurses formulate solutions, carry out nursing intervention, establish the patient's confidence and improve the patient's consciousness of medication. There were no complications during hospitalization, and preventive medication was still used according to the doctor's advice after discharge. At present, glucocorticoid is still the main drug for the treatment of Vogt Koyanagi Harada syndrome. The early sufficient treatment effect is good. Nurses can improve the drug compliance of patients adhering to formal treatment through effective nursing intervention, which can effectively prevent complications and significantly reduce disease recurrence.